Evaluation of the imunogenicity of one recombinant protein for the prevention of acute pneumonia in alpacas (Vicugna pacos) - Moreno-Morales, Gerald (2021)
The aim of this study was to evaluate the in vivo immunogenic capacity of a recombinant outer membrane protein of Pasteurella multocida called P6-like (rP6-like). The field trial was carried out in an alpaca production unit in Puno, Peru, and the processing of the samples was done in the Faculty of Veterinary Medicine of San Marcos University in Lima. Four groups of 5 animals were formed, and they were inoculated according to group with a) normal saline solution, b) bacterin, c) rP6-like, d) combination of bacterin + rP6-like. Blood samples were collected on days 0, 5, 7, 9, 12 and 15 post-inoculation. Single-point indirect ELISA tests were designed for the relative quantification of specific anti-rP6-like antibodies and for total anti-total P. multocida protein antibodies. The group inoculated with rP6-like showed significant elevation of antibodies from day 7 (p<0.05) until day 15 post-inoculation. The other biological products did not show significant elevation during the studied period. The study showed the immunogenic capacity of rP6- like, which allows to continue with future efficacy studies.